Features of the course of pregnancy and childbirth after conservative treatment of initial atypical hyperplasia and endometrial cancer - A. V. Charkhifalakyan; O. F. Serova (Лечащий Врач)
Background. Survival rates for endometrial cancer have improved in recent decades, so strategies are needed to avoid or reduce reproductive harm caused by cancer treatment. In medicine today, there are questions that do not always have answers. There are not enough works that would analyze and summarize the features that reflect the nature of the course of pregnancy and childbirth, the possibilities of ante- and intrapartum monitoring and the nature of obstetric care, as fundamental factors in the formation of perinatal indicators. In addition, there is extremely insufficient information about the effect of pregnancy on further risks of relapse, which convinces us of the advisability of further study of this problem. Our study allowed us to show the possibility of safe pregnancy and labour in such patients, to evaluate the peculiarities of the course of pregnancy and labour and the long-term prognosis for the woman's health.Objective. The purpose of our work was to study the characteristics of the course of pregnancy and childbirth in patients after conservative treatment of atypical hyperplasia and endometrial cancer.Results. The study included 114 patients with spontaneous and induced pregnancy that occurred after conservative treatment of atypical hyperplasia and initial endometrial cancer. The course of the 1st, 2nd and 3rd trimesters of pregnancy, perinatal outcomes and disease-free survival in patients were analyzed.Conclusion. Our study made it possible to demonstrate the possibility of a safe course of pregnancy and childbirth in such patients, to evaluate the characteristics of the course of pregnancy and childbirth and long-term prognosis for the woman’s health. These results indicate a low recurrence rate of atypical hyperplasia and endometrial cancer after pregnancy, regardless of pregnancy outcome. It should be emphasised that no pregnancy-associated recurrences were observed.